1995
DOI: 10.1164/ajrccm.152.6.8520793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute and chronic inhaled furosemide on bronchial hyperresponsiveness in mild asthma.

Abstract: We determined whether chronic administration of furosemide aerosol would be beneficial for the treatment of asthma. First, we showed that furosemide aerosol delivered from a metered-dose inhaler (10 and 20 mg) significantly protected against sodium metabisulfite (MBS) challenge by 0.6 and 1.3 doubling dilutions respectively in 12 volunteers with mild asthma. In a double-blind cross-over study, we examined the effect of furosemide aerosol from a twice more efficient metered-dose inhaler (10 mg four times per da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Increased diuresis has only been reported in four studies in adults. 29,43,46,47 The effect of the increased diuresis has been reported to last for up to 24 hours. 29 There was a nonstatistically significant increase in diuresis in the study from Rodriguez et al 47 in the furosemide group compared to placebo.…”
Section: Reported Adverse Eventsmentioning
confidence: 99%
“…Increased diuresis has only been reported in four studies in adults. 29,43,46,47 The effect of the increased diuresis has been reported to last for up to 24 hours. 29 There was a nonstatistically significant increase in diuresis in the study from Rodriguez et al 47 in the furosemide group compared to placebo.…”
Section: Reported Adverse Eventsmentioning
confidence: 99%
“…The weak effect of Fu following preincubation compared to incubation may explain the lack of evident asthma controlling properties [38]. From our experiments, one may conclude that some of the clinical actions of Fu that resemble the cromones may be explained by inhibition of Ca 2 + influx, ROS production and chemotaxis in/of inflammatory cells.…”
Section: Discussionmentioning
confidence: 75%
“…These data suggest that there may be a diuretic effect of nebulised frusemide. Previous studies have reported both a diuretic effect [25][26][27][28] and no diuretic effect [26,29] The Acute Haemodynamic Effect of Nebulised Frusemide in Stable, Advanced Heart Failure pharmacokinetic data available we are unable to determine if a sufficient amount of frusemide was available systemically to produce a diuretic effect. This controversy demands pharmacokinetic studies in controlled situations to demonstrate effect.…”
Section: Discussionmentioning
confidence: 93%